2014
DOI: 10.1093/inthealth/ihu075
|View full text |Cite
|
Sign up to set email alerts
|

Health worker perceptions of integrating mobile phones into community case management of malaria in Saraya, Senegal

Abstract: By documenting widespread use of mobile phones and health worker perceptions of their most useful applications, this paper provides a framework for their integration into the community case management of malaria programme in Saraya, Senegal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
6
20
0
Order By: Relevance
“…In Saraya, Senegal the qualitative study was conducted to explore health workers experience of using wireless technology for community case management (CCM) of malaria. The study reported that health workers greatly valued the use of mobile phones as it helped them address issues of training, stock management, reporting, and transportation [26]. In Uganda and Mozambique, a study was conducted to explore views of CHWs on the potential role of mHealth in their work delivering integrated community case management (iCCM) of children.…”
Section: Benefits Of Using Mobile Phones For Chwsmentioning
confidence: 99%
“…In Saraya, Senegal the qualitative study was conducted to explore health workers experience of using wireless technology for community case management (CCM) of malaria. The study reported that health workers greatly valued the use of mobile phones as it helped them address issues of training, stock management, reporting, and transportation [26]. In Uganda and Mozambique, a study was conducted to explore views of CHWs on the potential role of mHealth in their work delivering integrated community case management (iCCM) of children.…”
Section: Benefits Of Using Mobile Phones For Chwsmentioning
confidence: 99%
“…This new mode of health communication is being employed for providing community education and trainings, facilitation of health education sessions and as a job aid for improving the counselling skills of community health workers . Across the world, m‐health has been used in field of maternal & child health , malaria , diabetes , HIV/AIDS , sexual and reproductive health , health behaviour change , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Another concern stems from whether homeless youth would be interested in using mobile phones for health and social interventions given higher rates of residential, financial, and mobile instability. Among the growing research on pre-intervention preferences for mHealth programs (Blanas et al, 2015;Blas, Menacho, Alva, Cabello, & Orellana, 2013;Cormick et al, 2012;Jennings, Ong, Simiyu, Sirengo, & Kassaye, 2013;Labacher & Mitchell, 2013;Roberts, Birgisson, Chang, & Koopman, 2015;Vandelanotte et al, 2013;Wright, Fortune, Juzang, & Bull, 2011), only two studies were conducted with homeless populations (McInnes et al, 2014;Post et al, 2013). Results showed that individuals experiencing homelessness were interested in receiving mobile-based health information (McInnes et al, 2014;Post et al, 2013), although neither study focused on homeless youth.…”
mentioning
confidence: 99%